2008
DOI: 10.1021/bi8014289
|View full text |Cite
|
Sign up to set email alerts
|

Concerted but Noncooperative Activation of Nucleotide and Actuator Domains of the Ca-ATPase upon Calcium Binding

Abstract: Calcium-dependent domain movements of the actuator (A) and nucleotide (N) domains of the SERCA2a isoform of the Ca-ATPase were assessed using constructs containing engineered tetracysteine binding motifs, which were expressed in insect High-Five cells and subsequently labeled with the biarsenical fluorophore 4′,5′-bis(1,3,2-dithoarsolan-2-yl)fluorescein (FlAsH-EDT2). Maximum catalytic function is retained in microsomes isolated from High-Five cells and labeled with FlAsH-EDT2. Distance measurements using the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
4
11
1
Order By: Relevance
“…This change was somewhat smaller in magnitude than the 30+ Å change predicted by the first X-ray crystallographic structures ( Fig. 1 A), but larger than that measured by other FRET studies [8], [9], [29], Most notably, the distance change observed here was opposite in direction compared to early crystal structure predictions [4]. The apparent decrease in FRET distance with Ca also contrasts with previous FRET studies that used reactive dyes as donors/acceptors.…”
Section: Discussioncontrasting
confidence: 89%
“…This change was somewhat smaller in magnitude than the 30+ Å change predicted by the first X-ray crystallographic structures ( Fig. 1 A), but larger than that measured by other FRET studies [8], [9], [29], Most notably, the distance change observed here was opposite in direction compared to early crystal structure predictions [4]. The apparent decrease in FRET distance with Ca also contrasts with previous FRET studies that used reactive dyes as donors/acceptors.…”
Section: Discussioncontrasting
confidence: 89%
“…All these three distance profiles within residues in the transmembrane region were exhibited as a result of conformational changes triggered by the binding of RA to SERCA1a during the calcium transport process. As described by Chen et al, 2008 [58], the salt bridge between Arg762 and Asp981 was formed after calcium binding to site I [58]. Thus, this salt bridge was hindered by RA binding, which was confirmed by the Arg762NH -Asp981OD1 distance staying at ~13 Å during the 200 ns MD simulation ( Figure 5B).…”
Section: Molecular Dynamics Simulation Of Serca1a-ra-popc Systemsupporting
confidence: 70%
“…Thus, this salt bridge was hindered by RA binding, which was confirmed by the Arg762NH -Asp981OD1 distance staying at ~13 Å during the 200 ns MD simulation ( Figure 5B). On the other hand, the pairwise distances of Glu80-Arg290 and Glu90-Lys297, which were formed after Ca 2+ binding to site II [58], alternated and complemented between two states allowing the formation and/or breaking of a salt bridge ( Figure 5B). According to our calculations, RA occupied the Ca 2+ -binding site I (Glu908, Glu771 and Asp800, Asn768, Thr799 as described in [12]) instead of Ca 2+ -binding site II (Ala305, Glu309, Asn796, Asp800 as described in [12]).…”
Section: Molecular Dynamics Simulation Of Serca1a-ra-popc Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…46 The region that is most frequently used for TC environment design is a protein loop: the motif is incorporated either into a protein‐chain turn, or into a domain‐connecting region, by insertion of a TC sequence or by replacement of the existing amino acids (Figure 2 C). 14, 4761 This approach is often used when the protein structure is known, but it is possible to identify exposed loops by bioinformatic prediction and experimental research. It should be noted that the fluorescence of biarsenical TC loops varies significantly, even within a single protein, and it strongly depends on the surrounding amino acids 47.…”
Section: Placement Of Tc Motif In Proteinsmentioning
confidence: 99%